Association of peripheral neuropathy with sleep-related breathing disorders in myotonic dystrophies - Banach,Marta; Antczak,Jakub; Rola,RafaÅ‚ (Neuropsychiatric Disease and Treatment, 2017)
Marta Banach,1,* Jakub Antczak,1,* RafaÅ‚ Rola21Department of Clinical Neurophysiology, 2First Department of Neurology, Institute of Psychiatry and Neurology, Warsaw, Poland *These authors contributed equally to this workBackground: Myotonic dystrophy (DM) type 1 and type 2 are inherited diseases characterized by myotonia and myopathy. Additional symptoms include, among others, peripheral neuropathy and sleep-related breathing disorders (SRBDs). There is growing evidence for a complex association between DM1 and DM2, which was described in patients with diabetes mellitus and in the general population. In this study, we investigated whether there is an association between peripheral neuropathy and SRBDs also in the population of patients with DM.Methods: The study included 16 patients with DM1 (mean age, 37.9±14.1 years; 20–69 years) and eight patients with DM2 (mean age, 47.6±14.1 years; 20–65 years), who underwent a sensory and motor nerve conduction study (NCS) and diagnostic screening for SRBDs. In both groups, the NCS parameters were correlated with respiratory parameters.Results: In both groups, the amplitude of the ulnar sensory nerve action potential (SNAP) correlated with the mean arterial oxygen saturation (SaO2). In addition, in the DM2 group, the median SNAP correlated with the mean SaO2. In the DM1 group, the median SNAP and the distal motor latency (DML) of the ulnar nerve correlated with the apnea–hypopnea index, while the oxygen desaturation index correlated with the DML of the tibial nerve and with conduction velocity in the sural nerve.Conclusion: Our results indicate a complex association between neuropathy and SRBDs in DM1 and DM2. Axonal degeneration may contribute to nocturnal hypoxemia and vice versa. Neuropathy may contribute to muscle weakness, which in turn may cause respiratory events.Keywords: myotonic dystrophy, SRBD and neuropathy with AHI, SNAP, CMAP